The FORMULASI DAN UJI SIFAT FISIK PASTA GIGI GEL DARI EKSTRAK KERING JAHE MERAH (Zingiber Officinale Roscoe Var. Rubrum): FORMULATION AND PHYSICAL PROPERTIES TEST OF DRY EXTRACT RED GINGER IN GEL TOOTHPASTE (Zingiber Officinale Roscoe Var. Rubrum) - Rahma Lini (Jurnal Penelitian Farmasi Indonesia, 2021)
Formulation and physical properties test of dry extract from red ginger (zingiber officinale roscoe var rubrum) in gel toothpaste has been conducted. This study aims to formulate and test the physical properties of a good gel toothpaste preparation from dry red ginger extract with concentration 3% and 4%. Formulation is subjected to physical evaluation in the form of organoleptic test, pH test, homogeneity test, dispersion test, foaming test and acceptance test. The result of physical properties test is showed that concentrasion 3% has a good assessment because it is obtained stable for four weeks at storage, whereas concentration 4% in the second week of storage undergoes separation into two phases, namely oil and base. This indicates that the dry extract of red ginger at concentration of 3% can be formulated and has good physical stability for the gel toothpaste for 4 weeks of storage.